The Influence of Marketing Strategy on Increasing Sales In The Company - Wike Stevani (International Journal of Education, Information Technology, and Others, 2022)
With the advancement of technology in this era of globalization, every company strives to always improve the quality of its production and marketing management with the aim of maximizing profits according to the targets desired by each company. Marketing is one of the most important functions in a company, where with proper marketing it can determine the sales volume and position of the company (product) in the market. By analyzing the results of the survey based on the activities of reviewing and reviewing existing theories in the literature that has been collected, respondents consider it important to use marketing strategies in their companies so that their companies can develop and run well in line with current technology.